Obstructive Sleep Apnea Syndrome (OSAS): Occupational Health and other medical disciplines facing the problem - Costa, Giovanni; De Benedetto, Michele (La Medicina del Lavoro, 2017)
Obstructive Sleep Apnea Syndrome (OSAS) is one of the most common causes of excessive daytime sleepiness, therefore an important determinant of road and work accidents, as well as being associated with multiple chronic-degenerative diseases. The recent transposition of the European Commission Directive 2014/85/EU on driver licensing highlighted the need to tackle the problem appropriately, not only for its high prevalence in the general population, but also for its significant impact on occupational safety and health, and related social costs. The Occupational Health Physician is required to play a strategic role in this regard, not just for early diagnosis, but also for monitoring the therapeutic efficacy in maintaining or reintegrating workers into specific jobs. The effectiveness of his/her work will depend primarily on the level of interaction he/she will be able to establish with the different specialists who are in charge of the diagnostic and therapeutic process, in order to maintain a satisfactory work performance and to prevent possible deleterious effects on health in the medium and long-term period. The logic of this multidisciplinary approach has led nineteen scientific Societies and Associations to establish a Joint Technical Committee and to address the problem in the light of effectiveness and efficiency criteria in the interest of the individual and the community.